Proof of Concept and Pilot Study on the Development and Implementation of an Electronic Medication Administration Record - Lebel Denis; Mercier Geneviève; Dulermez Thomas; Rousseau Aurélie; Bussières Jean-François (De Gruyter, 2016)
Objective: The main objective is to describe the phases of electronic medication administration record development and implementation. The secondary objective is to compare dose information using medication administration record and electronic medication administration record.